1998
DOI: 10.1093/bja/80.5.685
|View full text |Cite
|
Sign up to set email alerts
|

Survival from massive intraoperative pulmonary thromboembolism during orthotopic liver transplantation

Abstract: We report a case of massive pulmonary embolism occurring at the time of graft reperfusion in a patient undergoing orthotopic liver transplantation. The clinical diagnosis of pulmonary embolus was aided by on-table echocardiography. Cardiopulmonary bypass and surgical embolectomy prevented her death. We discuss the differential diagnosis, possible aetiology of pulmonary embolism in this context and subsequent management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 6 publications
2
41
1
Order By: Relevance
“…1,15,16 It is believed that intraoperative ICTs during OLT are greatly underdiagnosed and underreported. 9 The need for TEE monitoring is an obstacle for the accurate diagnosis of intraoperative ICTs (particularly those without significant hemodynamic changes). In this study, using prospectively collected data, we demonstrated that the incidence of ICTs in patients who were monitored by TEE during OLT was 1.9%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1,15,16 It is believed that intraoperative ICTs during OLT are greatly underdiagnosed and underreported. 9 The need for TEE monitoring is an obstacle for the accurate diagnosis of intraoperative ICTs (particularly those without significant hemodynamic changes). In this study, using prospectively collected data, we demonstrated that the incidence of ICTs in patients who were monitored by TEE during OLT was 1.9%.…”
Section: Discussionmentioning
confidence: 99%
“…4,7,9,10,12,13,17,18 Others are inherent to the OLT procedure: excessive activation of the coagulation system, venous stasis during clamping of the portal vein and inferior vena cava, and release of activators from the liver graft. 6,7,9 In addition, other conditions such as heparin-induced thrombocytopenia, factor V Leiden, and antithrombin deficiency can contribute to thrombosis and possibly ICTs during OLT. Finally, intraoperative management may play an important role: PA catheter placement; the administration of antifibrinolytics, anti-hepatitis B immunoglobulin, and blood products; and the intraoperative utilization of continuous venovenous filtration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thromboelastograph helps assessing both cellular and humoral components of whole blood coagulation and fibrinolysis; and also the effects of antifibrinolytic therapy, cryoprecipitate, fresh frozen plasma, platelet and protamin as treatment strategies. However, there have been some case reports of thromboembolic complications in patients treated with antifibrinolytic agents (Manji et al, 1998;Sopher et al, 1997;O'Connor et al, 2000;Gologorsky et al;Ramsay et al, 2004;Ellenberger et al, 2006). A systematic review and meta-analysis of the safety of antifibrinolytic drugs has not shown any relationship with thrombosis in liver transplantation (Molenaar et al 2007).…”
Section: The Neohepatic Phasementioning
confidence: 99%